Analysis of SLAPP Actions by The State Through Hegemonic Philosophy: Study of Rejection Gold Mining in Banyuwangi - Fikri Gali Fernando Holqi; Indah Shellychah; Arifudin Arifudin (Mahesa Research Center, 2024)
This study seeks to identify the background and form of SLAPP actions carried out by the government against communities opposed to mining activities in Tumpang Pitu Banyuwangi. The research uses a qualitative description approach with a type of literature study. The data is obtained by reviewing literature sources, including books, journals, and relevant research results. The collected data is then classified based on primary and secondary data. It was then analyzed using Antonio Gramsci's theory of philosophy of hegemony. The results of the study stated that background related to the movement of community opposition over mining activities in Tumpang Pitu, Pesanggaran, Banyuwangi due to the transition of IUP from PT IMN to PT BSI through the Regent of Banyuwangi as stated in Decree Number 188/574/KEP/429.011/2012 and SK. 826/Menhut-II/2013. The form of SLAPP action from the government is identified in the repressive actions of POLRI officers and the punishment of one member of an environmental activist who is normatively protected by Article 66 of the PPLH Law. To create a good relationship between the Company and the community as a preventive effort to prevent a conflict, the formation of public policy must be bottom-up.